Kemampuan Menulis Teks Argumentasi Siswa Kelas VII A Sekolah Menengah Pertama SMP Negeri 1 Amanuban Tengah: Indonesia - Solina Snae; Ronni M. Ndun; Richard Oematan (Universitas Persatuan Guru 1945 NTT, 2026)
This study aims to determine the Ability to Write Argumentative Texts of Class VII A Students of State Junior High School (SMP) 1 Amanuban Tengah, The problem to be solved in this study is how the ability to write argumentative texts in class VII A students of SMPN 1 Amanuban Tengah. With the objective to be achieved in this study is to describe the ability to write argumentative texts in class VII A students of SMPN 1 Amanuban Tengah. The method used is descriptive quantitative, qualitative, namely a research mechanism in the form of numbers in the assessment process is arranged carefully and systematically starting from collecting data to interpreting and reporting the results of the study. The results of the study on the ability to write argumentative texts in class VII A students of SMP Negeri 1 Amanuban Tengah show that out of 32 students. very capable consisting of 4 students, capable consisting of 22 students, quite capable consisting of 6 students, and less capable none. The ability to write argumentative texts in class VII A students of SMP Negeri 1 Amanuban Tengah with an average score of 72.87 in the capable category. Thus, educators in learning to write argumentative texts in order to achieve learning outcomes in accordance with the predetermined KKM.